Short communication. Effect of type and level of supplementation with dietary n-3 fatty acids on yolk fat composition and n-3 fatty acid retention in hen eggs - Cachaldora, P.=700 1 De Blaás, J.C.; Garcia Rebollar, P.; Alvarez, C.; Mendez, J.
(Es, En)
ilus., 13 ref.
Keywords: ALIMENTACION DE LOS ANIMALES; GALLINAS PONEDORAS; SUPLEMENTOS; ACIDOS GRASOS; ACEITES; ALGAS MARINAS; VALOR NUTRITIVO; HUEVOS; ESPAÑA; ACIDOS GRASOS N-3